Value of magnetic resonance diffusion-weighted imaging for the prediction of radiosensitivity in nasopharyngeal carcinoma - Hong, Jinsheng; Yao, Yiqi; Zhang, Yu; Tang, Tianlan; Zhang, Hao; Bao, Daoliang; Chen, Yunbin; Pan, Jianji (Otolaryngology-head and neck surgery, 2013)
The effectiveness of radiotherapy in nasopharyngeal carcinoma (NPC) is closely related to the radiosensitivity of the carcinoma; however, there is currently no effective method to predict radiosensitivity in NPC. We explored the predictive value of magnetic resonance diffusion-weighted imaging (MR-DWI) for radiosensitivity in NPC. Study Design Prospective cohort study. Setting Single hospital. Patients with NPC who received intensity-modulated radiotherapy (IMRT) with or without chemotherapy were enrolled from April 2010 through November 2011. Primary tumor apparent diffusion coefficient (ADC) was measured before treatment (ADC0) and 2 weeks after the start of IMRT (ADC1). ADC change (ΔADC) was calculated as (ADC1 - ADC0)/ADC0 * 100%. Three months after the end of radiotherapy, the short-term effect of radiotherapy was assessed using the World Health Organization's response evaluation criteria in solid tumors. Of 134 eligible NPC patients, 121 received combination chemotherapy. Three months after radiotherapy, residual local tumors were detected in 23 (17.2%) cases, and no residual tumors were detected in 111 (82.8%) cases. There was no significant difference in the residual tumor rates of patients receiving combination chemotherapy vs those who did not (P = 1.000). There were no significant differences in the ADC0 or ADC1 values of patients with and without residual tumors (P = .083 and .262). The ΔADC values of patients with (49.77% ± 31.02%) and without (68.35% ± 34.22%) residual tumors were significantly different (t = -2.406, P = .017). Logistic regression analysis indicated that ΔADC was an independent prognostic factor for the short-term effect of IMRT in NPC. Magnetic resonance diffusion-weighted imaging may potentially have value for predicting radiosensitivity in NPC.